A Statistical Comparison of Cancer Mortality Rates Between Developed and Developing Countries - Mohd Kamaruzaman, Nur Syameerah Hanani; Rusiman, Mohd Saifullah (Enhanced Knowledge in Sciences and Technology, 2026)
This study addresses disparities in cancer deaths worldwide through the analysis of long-term patterns in 20 countries in developed and developing countries by secondary data from 1990 to 2016 incorporating five major types of cancers including lung, breast, colorectal, liver, and stomach cancers. The Principal Component Analysis (PCA) is used to eliminate data dimensions and find major patterns of mortality, which proves two main components that explain a significant percentage of all the variances, the first component is significantly related to the lifestyle-associated cancer such as lung, breast, and colorectal and the second element is associated with the infection-related and region-specific mortality such as liver and stomach. According to these aspects, K-means cluster analysis (K = 2) can group the countries into high- and low-mortality groups regardless of the specified economic groups, which indicates that the statistical groupings and development status are highly consistent. The findings reveal that developed nations are largely concentrated into the category of mortality due to lung and colorectal cancer whereas developing nations are largely gathered under the category of mortality due to liver and stomach cancer showing a different epidemiology of the same arising out of the lifestyle, access to healthcare, and prevention measures. The integrative multivariate method offers strong empirical data of self-perpetuating structural disparities in the world healthcare institutions and cancer control initiatives. The current research will be useful in practice because it provides a data-based model to facilitate the implementation of specific interventions in the field of public health, a more efficient distribution of resources, and cancer prevention and early diagnosis policies that are specific to the region, which will result in the reduction of international health disparities in cancer mortality and the enhancement of international health outcomes.